Two Patterns of Interocular Delay Revealed by Spontaneous Motion-in-Depth Pulfrich Phenomenon in Amblyopes with Stereopsis - Wu, Yidong (Invest Ophthalmol Vis Sci, 2020)
PURPOSE: To assess interocular delays in amblyopes with stereopsis and to evaluate the relationship between interocular delays and the clinical characteristics. METHODS: Twenty amblyopes with stereopsis (median, 400 arcseconds) and 20 controls with normal or corrected to normal visual acuity (≤0 logMAR) and normal stereopsis (≤60 arcseconds) participated. Using a rotating cylinder defined by horizontally moving Gabor patches, we produced a spontaneous Pulfrich phenomenon in order to determine the interocular delays, that is, the interocular phase difference at which ambiguous motion in plane was perceived. Two spatial frequencies—a low (0.95 cycles/degree [c/d]) and a medium (2.85 c/d) spatial frequency—were tested. RESULTS: The absolute interocular delays of the amblyopic group was significantly longer than that of the controls at both low or medium spatial frequencies (P < 0.01). However, the interocular delays was not always in favor of the fellow eye: 35% of the amblyopes (7/20) showed a faster processing of the amblyopic eye than that of the fellow eye at 0.95 c/d and 29.5% (5/17) at 2.85 c/d. No significant correlation was found between interocular delays and the clinical characteristics (e.g., age, treatment history, stereoacuity, and magnitude of anisometropia) in this amblyopic cohort. CONCLUSIONS: The interocular delays in amblyopes with stereopsis might result from either a faster or slower processing of the amblyopic eye relative to the fellow eye. This work provides important additional information for binocular processing of dynamic visual stimuli in amblyopia. However, the special role between this form of interocular delays and patients’ clinical characteristics remains unknown.